EFEKTIVITAS MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN APLIKASI POWTOON - Nela Sari Yolanda; Niscaya Laia (STKIP Pesisir Selatan, 2023)
Learning media is one of the intermediaries used to convey messages from teachers to students. In the world of education, learning media is known as an intermediary that is used to convey messages so that students understand the material conveyed by the teacher to students so that learning objectives are achieved. The function of the media was originally only known as a tool in teaching and learning activities, namely providing a visual experience in order to encourage learning motivation, clarify and simplify complex concepts. This study aims to determine the effectiveness of mathematics learning media using the powtoon application, by looking at student learning outcomes between classes that use learning media using the powtoon application and classes that do not use learning media using the powtoon application. Based on the results of the analysis, it shows that the learning media developed have been effective, as can be seen from the learning outcomes of students increasing after using learning media using the powtoon application.